The impatience mechanism as a diversity maintaining and saddle crossing strategy - Karcz-Dulęba, Iwona (Zielona Góra: Uniwersytet Zielonogórski)
The impatience mechanism diversifies the population and facilitates escaping from a local optima trap by modifying fitness values of poorly adapted individuals. In this paper, two versions of the impatience mechanism coupled with a phenotypic model of evolution are studied. A population subordinated to a basic version of the impatience mechanism polarizes itself and evolves as a dipole centered around an averaged individual.
Keywords: phenotypic evolution; impatience operator without and with extra knowledge; polarization of population; maintaining population diversity; saddle crossing